Problem strefy nadgranicznej w aktach Prezydium Wojewódzkiej Rady Narodowej w Zielonej Górze = The problems of the borderland zone in the records of the Presidium of the Provincial National Council in Zielona Góra - Trojanowski, Michał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The documents gathered in the archives in Stary Kisielin concern delineating as well as marking and controlling the borderland regions of Lubusz Land. They cover the years 1945-1970. They contain a number of decisions and administrational edicts that regulate the legal matters regarding the settlement and the reasons for relocation of people from the borderline areas.
Keywords: czasopismo; czasopismo akademickie; Ziemie Zachodnie; stosunki polsko-niemieckie; pogranicze polsko-niemieckie; historia